Did the Basel process of capital regulation enhance the resiliency of European Banks? - Thomas Gehrig; Maria Chiara Iannino (Bank of Finland, 2018)
This paper analyses the evolution of the safety and soundness of the European banking sector during the various stages of the Basel process of capital regulation. In the first part we document the evolution of various measures of systemic risk as the Basel process unfolds. Most strikingly, we find that the exposure to systemic risk as measured by SRISK has been steeply rising for the highest quintile, moderately rising for the second quintile and remaining roughly stationary for the remaining three quintiles of listed European banks. This observation suggests that the Basel process has succeeded in containing systemic risk for the majority of European banks but not for the largest and most risky institutions. In the second part we analyze the drivers of systemic risk. We find compelling evidence that the increase in exposure to systemic risk (SRISK) is intimately tied to the implementation of internal models for determining credit risk as well as market risk. Based on this evidence, the sub-prime crisis found especially the largest and more systemic banks ill-prepared and lacking resiliency. This condition has even aggravated during the European sovereign crisis. Banking Union has not restored aggregate resiliency to pre-crises levels. Finally, low interest rates considerably a ect the contribution to systemic risk for the safer banks.
URN:NBN:fi:bof-201809272064
Keywords: B26; E58; G21; G28; H12; N24; 330